Morphological alterations and gene expression levels in the cerebral cortex causally influence susceptibility to type 2 diabetes: A Mendelian randomization study - Fanghang Ye; Yucheng Huang; Na Li; Liyuan Hao; Jiali Deng; Shenghao Li; Jiayun Yue; Fei Yu; Xiaoyu Hu (Experimental Gerontology)
Background: The associations between type 2 diabetes (T2D) and neurological as well as psychiatric disorders have garnered growing interest. Previous evidence has indicated a correlation between the cerebral cortex and these conditions. However, the causal direction between the cerebral cortex and T2D remains ambiguous. Methods: We conducted a cerebral cortex-focused systematic Mendelian randomization (MR) study based on multiple data sourced from genome-wide association studies and expression quantitative trait locus. Results: The surficial area (SA) of Pars Opercularis and the thickness (TH) of the Supramarginal gyrus were found as significant contributors to the risk of T2D. Conversely, thickening in the Precentral area, Caudal Anterior Cingulate cortex, and banks of the Superior Temporal Sulcus, as well as SA amplification of the Precentral area, were associated with a reduced risk of T2D. There was no evidence of reverse causation. These alterations also have an impact on susceptibility to T2D complications. Combining the summary-data-based MR (SMR) analysis and colocalization analysis, we prioritized the expression of three causal genes in the cerebral cortex with genetic evidence for influencing T2D susceptibility. Elevated expression levels of NUDC and PACC1 increased susceptibility to T2D, whereas RAB29 expression exhibits an inverse association with T2D susceptibility. Mediation MR analysis revealed that TH of the Banks of the Superior Temporal Sulcus, SA of Precentral area, SA of Pars Opercularis, and SA of Supramarginal gyrus mediated the effect of RAB29 on T2D. Cross-tissue colocalization analysis demonstrated that the expression pattern of NUDC displayed brain tissue specificity. PACC1 and RAB29 also exhibited colocalization signals in several specific tissues beyond brain tissue. The phenome-wide association study suggested that these genes underscore the shared genetic burden of T2D with a range of disease phenotypes including mental disorders, cardiovascular disease, and malignancies. Conclusions: These findings underscore the novel role of the central nervous system in genetic liability to T2D and provide valuable clues for future mechanism studies.